COMPARATIVE STUDY OF LAPAROSCOPIC VS. OPEN APPENDECTOMY: POSTOPERATIVE OUTCOMES AND COMPLICATION RATES (The Research of Medical Science Review, 2025)
Background: Age-related health needs warrant appendectomy surgery for treating acute appendicitis. Laparoscopic appendectomy gained increased prevalence because it offered patients decreased recovery time along with reduced complications after surgery. The surgical procedure of open appendectomy remains popular both because medical facilities are limited and because of its widespread acceptance. A vital comparison process must occur to determine the most suitable surgical method between examining postoperative results and surgical complication frequencies. Objectives: The study will investigate both postoperative outcomes and complication numbers along with recovery indicators among patients receiving laparoscopic appendectomy versus open appendectomy treatments for acute appendicitis. Study design: A retrospective comparative study. Place and duration of study: July 2024 to December 2024 General Surgery Department, Sandeman Provincial Hospital / Bolan Medical Complex Hospital, Quetta. Methods: The study included 100 patients who underwent appendectomy medical treatments between July 2024 through December 2024. Laparoscopic appendectomy patients alongside open appendectomy patients participated in the study totaling fifty participants for each group. The study analyzed patient demographic information together with surgical duration and hospitalization period and postoperative wound infection occurrence and complication development. A statistical significance emerged from results through the SPSS version 25.0 program which established a p-value below 0.05. Results:One hundred patients enrolled in the study which composed two distinct groups with 50 participants each. Study data showed that patients in the laparoscopic group experienced an average age of 28.4 ± 6.2 years while patients in the open group averaged 29.7 ± 7.1 years (p = 0.34). The laparoscopic group stayed in hospital for an average of 2.1 ± 0.8 days compared to 3.9 ± 1.2 days for the open group patients (p < 0.01). Wound infections occurred less frequently in the laparoscopic patients (4%) compared to open patients (18%) with statistical significance (p = 0.03). The operating duration for laparoscopic surgery surpassed open group procedures but statistical tests found no substantial difference between them (p = 0.08). The laparoscopic surgery group experienced less pain during recovery and a shorter time to complete their recovery process. Conclusion: The health benefits achieved during laparoscopic appendectomy surgery exceed those of open appendectomy because they provide shorter hospital stays, fewer complications and faster patient healing. The time-consuming operating process does not deter medical professionals from making laparoscopic appendectomy their procedure of choice for patient care. The acceptance of implementation growth as a safe procedure should be actively promoted.